PEROLEHAN HAK ATAS TANAH MELALUI SEWA BELI RUMAH DINAS PEKERJAAN UMUM KOTA PALANGKARAYA KALIMANTAN TENGAH - , BOBY ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The goal of research on \"Acquisition Rights of Land Through Lease Purchase Official House of Public Works Department Palangkaraya City, Central Kalimantan\" is to investigate and analyze the execution of the official house lease-purchase agreement of Public Works Department and to determine land rights acquired after payment of official house leasepurchase agreement of Public Works Department. This study is an empirical juridical. The data used in this study is the primary data and secondary data. The data collected through field research and library research. Subject of this study is divided into two respondents and informants. Respondents of 20 people, consisting of 10 civil servants of the Public Works Department who have made the transition of official house through lease-purchase and 10 civil servants of the Public Works Department Palangkaraya city who resides the official house (in the stage of settlement lease-purchasing payments ). Informant consists of one person Chief Office of Land Office Palangkaraya City, 1 Chief Office of Public Works Department Palangkaraya City, and a Notary and Land Deed Officer (PPAT). This research used purposive sampling. The results showed that the execution of the official house lease-purchase category III agreement including the land, payments by installments, which during the Second Party to pay the installment then it is counted as lease payments. Lease-purchase agreement was made unilaterally by the standard format according to applicable regulations (Verdict SEMA No B. 52/13/8 on Determination Cost of Making Official House category III Lease-Purchase Agreement Jo PMPU Number: 22/PRT/M/2008 on Guidelines Technical Procurement, Registration, Status Determination and Transition Rights of Official House). The PPAT or Notary has no role in official house lease-purchase agreement including the land. Acquired land rights in official house category III lease-purchase agreement including the land is proprietary. Which is obtained by carrying out land rights petition by the new residents as a continuation of a release of rights by the Public Works Department to the local Land Office.